The World Bank Annual Report 2004 : Volume 1. Year in Review - World Bank (Washington, DC, 2013)
This Annual Report, which covers the period from July 1, 2003, to June 30, 2004, has been prepared by the Executive Directors of both the International Bank for Reconstruction and Development (IBRD) and the International Development Association (IDA) in accordance with the respective bylaws of the two institutions. The Board emphasized the following areas during the fiscal year: Strategic Framework, the Bank's Role in Poverty Reduction; Country Programs; Global Programs and Partnerships; Oversight and Fiduciary Responsibility, and Administrative Budget. Volume 2: Financial Statements Reporting. IBRD prepares its financial statements in accordance with accounting principles.